ChemInform Abstract: An Ullmann C—O Coupling Reaction Catalyzed by Magnetic Copper Ferrite Nanoparticles. Issue 24 (23rd May 2013) - Yang, Shuliang; Wu, Cunqi; Zhou, Hua; Yang, Yanqin; Zhao, Yongxia; Wang, Chenxu; Yang, Wei; Xu, Jingwei
Abstract An efficient Ullmann C—O coupling reaction is developed, which tolerates a wide range of different functional groups.